2003
DOI: 10.1080/00365521.2003.11800650
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Localization of Pancreatic Secretory Proteins in Pancreatic Acinar-like Metaplasia in the Distal Part of the Oesophagus

Abstract: Pancreatic acinar-like metaplasia is common in the distal oesophagus and pancreatic secretory proteins, including trypsininogen 2, are produced in the oesophageal metaplastic acinar cells. The biological significance of this finding has yet not been thoroughly studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…PAM is characterised by cells with basophilic cytoplasm in the basal part, centrally or basally located nucleus and acidophilic granular cytoplasm in the luminal part [1]. Immunohistochemistry consistently shows reactivity for pancreatic lipase and trypsinogen [1,2,5], and it has been demonstrated that PAM in the distal oesophagus produces pancreatic secretory proteins [5]. PAM in non-cardia gastric mucosa was observed in up to 11% of investigated subjects [1,2,6], purportedly linked to intestinal and ''pyloric type'' metaplasia [1] and autoimmune gastritis [6].…”
Section: Introductionmentioning
confidence: 99%
“…PAM is characterised by cells with basophilic cytoplasm in the basal part, centrally or basally located nucleus and acidophilic granular cytoplasm in the luminal part [1]. Immunohistochemistry consistently shows reactivity for pancreatic lipase and trypsinogen [1,2,5], and it has been demonstrated that PAM in the distal oesophagus produces pancreatic secretory proteins [5]. PAM in non-cardia gastric mucosa was observed in up to 11% of investigated subjects [1,2,6], purportedly linked to intestinal and ''pyloric type'' metaplasia [1] and autoimmune gastritis [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, this kind of pathological metaplasia probably represents the disruption of a mechanism of developmental plasticity that is involved in non‐oncogenic tissue repair. Metaplastic conversions have been observed in all parts of the digestive system (Jankowski et al, 2000; Hakansson et al, 2003; Chatelain et al, 2004). The epithelium lining the lumen of the gastrointestinal tract continuously exfoliates as a response to continuous exposure of epithelial cells to digestive enzymes, microbes, toxins, and mechanical abrasion.…”
Section: Introductionmentioning
confidence: 99%
“…Wird eine Metaplasie von Pankreasgewebe klinisch auffällig, dann meistens bedingt durch die Komplikation einer chronischen Entzün-dung in dem betroffenen Organ. Es wurden Fälle von metaplastisches Pankreasgewebe in der distalen Speiseröhre (Barrett-Ösophagus), Magen (Autoimmungastritis), Dünndarm und Gallenblase beschrieben [2,6].…”
Section: Behandlungunclassified
“…6 positionierende Faktoren für die Entwicklung eines Malignoms [1,5,7,17]. Die Hepatikolithiasis als Ursache für ein cholangiozelluläres Karzinom wurde erstmals von Sane und MacCallum 1942 beschrieben [16].…”
Section: Introductionunclassified